Influence of Skin Subjective Symptoms on Sleep Quality in Patients with Cutaneous Disorders: A Study of 2871 Subjects - Halioua B; Misery L; Seite S; Delvigne V; Chelli C; Taieb J; Taieb C (Dove Medical Press, 2021)
Bruno Halioua,1 Laurent Misery,2,3 Sophie Seite,4 Veronique Delvigne,4 Clara Chelli,5 Jonathan Taieb,6 Charles Taieb7,8 1Dermatologue, Paris, France; 2Univ Brest, LIEN, F-29200, Brest, France; 3Department of Dermatologie, University Hospital of Brest, Brest, France; 4La Roche-Posay Laboratoire Dermatologique, Levallois-Perret, France; 5Department of Dermatology-Venereology, Robert-Debré Hospital, Reims, France; 6APHP, Hôtel Dieu, Centre du Sommeil et de la Vigilance, Paris, France; 7European Market Maintenance, Assessment, Patients Priority Department, Fontenay-sous-Bois, France; 8Hôpital Necker Enfants Malades, Paris, FranceCorrespondence: Bruno HaliouaDermatologue, 56 Boulevard Saint-Marcel, Paris, 75005, FranceEmail haliouab@yahoo.frIntroduction: Previous studies showed more sleep disturbance (SD) in patients with cutaneous disorders (CD). During CD, unpleasant subjective symptoms [USS], such as itch, pain and others (tingling, burning, or tightness) have a negative influence on sleep quality. This study aims to evaluate the prevalence of SD in CD patients and to identify the influence of itch, pain and other unpleasant sensations on SD.Materials and Methods: An international, anonymized real-life survey was conducted with individuals [18− 75 years], with physician-confirmed CD, or without CD. The 25 items covered sociodemographic characteristics, feeling of overall sleep quality and skin unpleasant sensations. Severity of SD and unpleasant sensations were assessed using a 10-cm Visual Analogue Scale (VAS).Results: From 3834 analyzed questionnaires, 2871 (67.3%) were in the CD group and 863 (32.7%) in the control group. Patients with CD had significantly more SD (71.2% vs 32.7% in the control group, p< 0.0001). CD patients without any reported unpleasant sensation were at higher risk for SD than control subjects (OR 1,362 [95% CI 1.975– 2.405] p=0.0013). SS were highly associated with SD (OR 1.641 [95% CI 1.393– 1.933] p< 0.0001). Pruritus, pain and intermediate sensations were significant predictors of SD, with odds ratios of 1.670, 1.625 and 1.326, respectively. VAS sleep scores were strongly associated with pruritus (r: 0.25, p< 0.0001) and pain (r: 0.25 p< 0.0001) severity ratings.Discussion: SD is a common problem for patients with CD. Patients with subjective symptoms suffer more from SD, suggesting that they are aggravating factors, but are likely not the only reason for SD in CD patients. We found that during CD, intermediate sensations also contribute to SD. Despite some limitations and the potential bias due to the study design, our results confirm for the first time on an international level the influence of subjective symptoms on sleep quality in patients with CD.Keywords: unpleasant sensations, sleep quality, cutaneous disorders